2016
DOI: 10.5194/hess-20-651-2016
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in calculating precipitation climatology in East Asia

Abstract: Abstract. This study examines the uncertainty in calculating the fundamental climatological characteristics of precipitation in the East Asia region from multiple fine-resolution gridded analysis data sets based on in situ rain gauge observations and data assimilations. Five observation-based gridded precipitation data sets are used to derive the long-term means, standard deviations in lieu of interannual variability and linear trends over the 28-year period from 1980 to 2007. Both the annual and summer (June-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…This may be due to the reanalysis models' inability to represent the effects of complex orography and/or sparse observational inputs for assimilations. It must be noted that the observed CMAP and GPCP data also suffer from the lack of gauge data in these regions (e.g., Kim et al 2015a;Kim and Park 2016). For higher modes (Fig.…”
Section: Comparison Of Individual Cseof Modesmentioning
confidence: 99%
See 3 more Smart Citations
“…This may be due to the reanalysis models' inability to represent the effects of complex orography and/or sparse observational inputs for assimilations. It must be noted that the observed CMAP and GPCP data also suffer from the lack of gauge data in these regions (e.g., Kim et al 2015a;Kim and Park 2016). For higher modes (Fig.…”
Section: Comparison Of Individual Cseof Modesmentioning
confidence: 99%
“…Previous studies (e.g., Kim et al 2015a;Kim and Park 2016) showed that the differences between observation-based gridded precipitation datasets vary widely according to regions, seasons, precipitation characteristics and/or statistical properties. Overall, the long-term means and the temporal standard deviation over the 37 summers, a surrogate for the seasonal cycle and its interannual variability respectively, of the GPCP data agree closely with the CMAP data ( Table 2).…”
Section: (3)mentioning
confidence: 99%
See 2 more Smart Citations
“…Also, its stochastic foundation provides some confidence that the uncertainty information is statistically reliable. Our experiments (section 5) pinpoint to the risk of underestimating uncertainty considerably with the popular ad hoc comparison of a set of deterministic results (e.g., Kim & Park, 2016;Kotlarski et al, 2017;Prein & Gobiet, 2016). The members of such a pseudo-ensemble all represent a sort of optimal estimate, based on mostly the same observations, rather than independent realizations (see also Chappell et al, 2012).…”
Section: Discussionmentioning
confidence: 96%